The tapestry of knowledge: manufacturing engineering research - Hashim, Rosziana (Penerbit UTeM Press, 2023)
This book offers readers recent research results and forefront development in the field of manufacturing engineering with broad coverage of topics related to advanced materials, process, design, robotics and automation as well operational management. Emphasis is given on papers that link theories to practical applications. Thus, this book also stages problem solving through various examples and real applications with the uses of advanced tools and techniques in research methodology. It is hoped that this book can serve as a platform for academic exchange between experts, scholars, researchers and students that would advance the state of the art and benefit society.